NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL ANTARES KARYA RWEINDA - Hidayah Budi Qur’ani; Purwati Anggraini; Joko Widodo (Universitas Muhammadiyah Mataram, 2022)
Abstrak:Novel populermerupakan salah satu jenis karya sastra yang sangat digemari remaja. Hal itu disebabkankarenacerita yang diangkat oleh pengarangsangatdekatdengankehidupanremaja. Pendidikan karaktermemangtidakbolehdipisahkandalamkehidupansehari-hariterutama pada saatremaja. Mulai darikehidupankeluarga, sekolah, hinggapergaulan. Penelitianinibertujuanuntukmendeskripsikannilai-nilai Pendidikan karakter dan kreativitaspengarangdalammenciptakankaraktertokoh yang terdapat pada novel Antares karyaRweinda. Sumber data pada penelitianiniadalah novel yang berjudulAntares karyaRweindaditerbitkan oleh Lovable tahun 2020. Data penelitianberupasatuan kata dan kalimat yang menggambarkannilai-nilaikarakter pada tokoh novel. Hasil daripenelitianiniadalahterdapat lima bentuknilaipendidikan yang digambarkandalam novel Antares karyaRweindadiantaranyatoleransi, tanggungjawab, kejujuran, solidaritas, dan berani. Kelimanilaipendidikankaraktertersebutsangatpatutuntukdicontohbagiremaja sat ini. Sehingga, novel inidapatdigunakansebagaialternatifdalampembelajarankarakter.Penggambarannilaipendidikankarakterdalam novel Antares karyaRweinda yang ditunjukkanmelaluikaraktertokohtidakterlepasdarikreativitaspengarang. Rweindasebagaipengarang novel inimampumenciptakantokohdenganberbagaikaraktertidakterlepasdarilingkungantempattinggalnya. Rweinda yang masihremajamampumenciptakantokohremajadengankarakter dan problem yang dialamisesuaidengankehidupanremaja. Abstract:Popular novels are one type of literary work that is very popular with teenagers. This is because the story that the author uses is very close to the lives of teenagers. Character education should not be separated in everyday life, especially during adolescence. Starting from family life, school, to social life. This study aims to describe the values of character education and the creativity of the author in creating the characters found in the novel Antares by Rweinda. The data source in this study is a novel entitled Antares by Rweinda published by Lovable in 2020. The research data is in the form of units of words and sentences that describe the character values of the novel characters. The results of this study are that there are five forms of educational values described in the novel Antares by Rweinda including tolerance, responsibility, honesty, solidarity, and courage. The five values of character education are very exemplary for today's youth. Thus, this novel can be used as an alternative in character learning. The depiction of the value of character education in the novel Antares by Rweinda which is shown through the characters cannot be separated from the creativity of the author. Rweinda as the author of this novel can create characters with various characters that cannot be separated from the environment in which they live. Rweinda who is still a teenager can create teenage characters with characters and problems experienced by the lives of teenagers.